Ethnotaxonomic systems can reflect the vitality status of indigenous languages and traditional knowledge - Franco, F. Merlin; Syafitri, Hidayati; Bibi Aminah, Abdul Ghani; Ranaivo-Malançon, Bali (National Institute of Science Communication and Information Resources (NISCAIR), 2015)
Biodiversity rich regions of the world are also known to harbour rich ethnic, cultural and linguistic diversities. Traditional Knowledge (TK) of indigenous communities could be one reason behind this factor as it facilitates ecosystem management and agriculture. TK is dependent on languages, without which, its transmission and accumulation is impossible. In this paper, it is argued that the ethnotaxonomic system of an indigenous community is an interjunction between its language and traditional knowledge. Both language and traditional knowledge are required to generate lexemes that are the building blocks of any classification system. TK generates scientific information related to ecology, morphology or utility of the life form while the language names it, and transmits information related to it across individuals and generations; Language gives the name while TK connects it to the appropriate denotatum. We argue that the vitality status of the community’s indigenous language and TK is reflected in its ethnotaxonomic system. We also present a newly developed Traditional Knowledge and Language Vitality index (TraLaVi) which could complement the existing indices which intend to assess the vitality status of indigenous languages and TK.